Preface - Jacob, I. Jeena; bin Ahmad, Badrul Hisham; Khan, Z. Faizal (Computer Assisted Methods in Engineering and Science, 2022)
We are pleased to present this special issue of Computer Assisted Methods in Engineering and Science on Advanced Optimization Methods for Uncertainties in Intelligent Industrial Systems. It includes the state-of-the-art studies with extended research on the challenges encountered when computational intelligence meets industrial systems.We hope that readers will enjoy this in-depth exploration of modern optimization and uncertainty handling approaches in different industrial environments.